Psoriasis (Homoeopathy for All, 2021)
Psoriasis is a chronic proliferativeand inflammatory condition thataffects the skin and sometimes thenails and joints. It occurs due to aproblem with the immune systemthat results in an overgrowth of skincells, leading to skin changes. Thismakes the skin build up into bumpyred patches covered with whitescales. They can grow anywhere,but most appear on the scalp,elbows, knees, and lower back. Itcan't be passed from person toperson. There are several subtypesof psoriasis but the plaque type isthe most common and presents onthe trunk, extremities, and scalp.People with psoriasis are morelikely to have diabetes, high bloodlipids, cardiovascular disease, anda variety of other inflammatory andNCDs.
Keywords: EPIDEMIOLOGY; Gender; scalp